علاقة ما فوق الأستيعاب بالذاكرة العاملة لدى طلبة الجامعة - جبر الزبيدي, رحيم عبد الله (Journal of College of Education, 2018)
The aim the resarceh was to identify the level the higher absorption and also to identify the working memory and what is relationshiep between the students of university and for the purpose of verifying that the researchers adopted the meta chomprehension (Mirr, 2004) (24). The researchers also adopted Ibrahim (2014) test for working memory in its final form, which consists of (28) paragraphs according to the Baddeley & Hitch model (1994). The psychometric properties of the measurements were verified and then Application of tools on the research sample, which reached (400) students The resuelts of studey showed that memberse of the research sampel have a good level of absorption and have an awareness of how their memory works if their average score is higher than the mean. The resueltse also showed a positive correlatione betwen the two, groups, A number of recommendations and proposals.